2018
DOI: 10.1016/j.msea.2017.12.106
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness at cryogenic temperatures of ultrafine-grained Ti-6Al-4V alloy processed by ECAP

Abstract: This research is focused on a study of the relationship between mechanical behavior, microstructure and fracture toughness of a Ti-6Al-4V alloy in both coarse-grained (CG) and ultrafine-grained (UFG) conditions. The UFG state with a primary alpha-phase grain size, but with different orientations with respect to the testing direction, was produced by equal-channel angular pressing (ECAP) after thermo-mechanical treatment. Fracture toughness and mechanical testing were conducted at a temperature of 196 °C. A du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…In the last two decades, many studies have appeared on the topic of ECAP processed titanium alloys. All investigations agreed that the ECAP method led to an ultra-fine grained (UFG) microstructure and enhanced strength [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In the last two decades, many studies have appeared on the topic of ECAP processed titanium alloys. All investigations agreed that the ECAP method led to an ultra-fine grained (UFG) microstructure and enhanced strength [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 54%
“…The center of the 2D PSD was set to a fixed value 2θD = 55° during the experiments. This 2θD angle allowed the observation of reflections (101 ̅ 1) and (0002), and the nominal gauge volume (NGV) was ~32.96 mm 3 .…”
Section: Neutron Diffractionmentioning
confidence: 99%
“…Majority of researchers have aimed at evolving newer means to reproducibly manufacture second phase strengthened nanograined steels and as well as, gaining insight into the underlying physical sciences. Continued effort to tailor strategy for toughening and strengthening of ultra fine grained steels encompasses employment of different processing routes like thermomechanical processing [5,6], severe plastic deformation by equal channel angular pressing [7,8], cyclic quenching [9], dynamic strain induced transformation [10][11][12], roll bonding [13,14], bidirectional large scale deformation and dynamic recrystallization through multi axle forging [15][16][17] for the production of ultra fine grained steels. These processes enable to achieve excellent combination of strength and ductility; accordingly, structurally refined steels of various types are seen to have assumed considerable commercial importance [18].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in the last 10 years, the fracture behavior of ultrafine-grained (UFG) and nanocrystalline (NC) metals processed by SPD techniques has come to the center of experimental interest in several research groups. [8][9][10][11][12][13][14][15] It was found that UFG and NC metals show a wide spectrum of fracture properties depending on factors such as the testing orientation, extent of SPD deformation, and temperature. The need to test different orientations in SPDprocessed materials, which are essential for materials exhibiting pronounced grain aspect ratios, showcased the ability to obtain one of the highest levels of damage tolerance, achievable in technically relevant metallic alloys.…”
Section: Introductionmentioning
confidence: 99%